Multifaceted folding in a foldamer featuring highly cooperative folds - Ramesh, Veera V. E.; Priya, Gowri; Kotmale, Amol S.; Gonnade, Rajesh G.; Rajamohanan, Pattuparambil R.; Sanjayan, Gangadhar J. (Chemical Communications, 2012)
Herein, we report on the folding pattern observed in a synthetic peptide featuring two highly mutually dependent, yet strikingly dissimilar, closed networks of hydrogen-bonded rings that work in a cumulative fashion to stabilize the entire folded architecture of the peptide. Structural studies unequivocally suggest that disruption of any one of these mutually-dependent hydrogen-bonded networks is deleterious to the stability of the fully folded conformation of the peptide.

Mixed-stack charge transfer crystals of pillar[5]quinone and tetrathiafulvalene exhibiting ferroelectric features - Shivakumar, Kilingaru I.; Swathi, Kadaba; Goudappagouda; Das, Tamal C.; Kumar, Ashwani; Makde, Ravindra D.; Vanka, Kumar; Narayan, Kavassery S.; Babu, Sukumaran Santhosh; Sanjayan, Gangadhar J. (Chemistry- A European Journal, 2017)
Ferroelectric materials find extensive applications in the fabrication of compact memory devices and ultra-sensitive multifunctional detectors. Face-to-face alternate stacking of electron donors and acceptors effectuate long-range unidirectional ordering of charge-transfer (CT) dipoles, promising tunable ferroelectricity. Herein we report a new TTF-quinone system-an emerald green CT complex consisting pillar[5]quinone (P5Q) and tetrathiafulvalene (TTF). The CT crystals, as determined by single crystal synchrotron X-ray diffraction, adopt a 1:1 mixed-stack arrangement of donor and acceptor with alternating dimers of TTF and 1,4-dioxane encapsulated P5Q. The TTF-P5Q.dioxane crystal possesses a macroscopic polarization axis giving rise to ferroelectricity at room temperature. The CT complex manifests ferroelectric features such as optical polarization rotation, temperature-dependent phase transition and piezoelectric response in single crystals. Ferroelectric behavior observed in P5Q-based CT complex widens the scope for further work on this structurally intriguing and readily accessible cyclic pentaquinone.
Keywords: Acceptor; Charge-transfer complexes; Chemistry; Conductors; DDQ; Donor; ferroelectric; Macrocycles; Organic Metals; Pi-interaction; Pillar[5]quinone; salts; Transfer Complexes; Transport

Modular approach towards functionalized highly stable self-complementary quadruple hydrogen bonded systems - Rayavarapu, Suresh; Kheria, Sanjeev; Shinde, Dinesh R.; Gonnade, Rajesh G.; Sanjayan, Gangadhar J. (Organic & Biomolecular Chemistry, 2017)
Self-complementary quadruple hydrogen bonded systems have shown potential as key building blocks for developing various supramolecular polymers. Opportunities for the introduction of multiple functionalities would further augment, in principle, their application potential. Herein, we report a novel modular approach to simultaneously introduce two closely aligned side chains into AADD-type self-complementary quadruple hydrogen-bonding systems. Dithiane-tethered ureidopyrimidinone has been used as a reactive intermediate to efficiently attach closely aligned side chains by simply reacting with amines to form highly stable molecular duplexes. These duplexes featuring AADD-type arrays of hydrogen bonding codes are highly stable in non-polar solvents (K-dim > 1.9 x 10(7) M-1 in CDCl3) as well as in polar solvents (K-dim > 10(5) in 10% DMSO-d(6)/CDCl3). Another notable feature of these self-assembling systems is their insensitivity to prototropy-related issues owing to their prototropic degeneracy, which will enhance their application potential in supramolecular chemistry.

Multi-purpose synthetic alpha-amino acid featuring coumarin and ureidopyrimidinone motifs on its backbone: Synthesis and peptide formation - Rashid, P. P.; Sanjayan, Gangadhar J. (Tetrahedron Letters, 2022)
Herein we report a synthetic a-amino acid featuring intensely fluorescent coumarin moiety and a strongly self-assembling ureidopyrimidinone (UPy) motif. This two-in-one synthetic amino acid, displaying both fluorescence and self-assembling property, has been synthesized in four easy steps starting from commercially available inexpensive starting materials. Suitably protected amino acid has been incorporated into various peptide sequences, following solution-phase peptide coupling protocols, to demonstrate its synthetic feasibility.(c) 2022 Elsevier Ltd. All rights reserved.
Keywords: Fluorescent amino acids; Fluorescent Peptides; Quadruple hydrogen bonding; Unnatural amino acids; Ureidopyrimidinone

Morphology rearrangement by mixing of internally hydrogen-bonded nanoparticles comprising triazine-based amphiphilic diblock copolymers - Haque, Farah; Thompson, Steven W.; Ishizuka, Fumi; van der Tol, Joost J. B.; Singh, Dharmendra; Sanjayan, Gangadhar J.; Zetterlund, Per B. (Macromolecules, 2025)
The self-assembly of block copolymers holds significant potential for designing functional nanoparticles in materials science, nanomedicine, and nanotechnology. While the self-assembly of amphiphilic diblock copolymers is relatively well understood, the influence of specific supramolecular interactions, particularly hydrogen bonding, in directing their morphological behavior remains largely unexplored. In this study, it was demonstrated that nanoparticles self-assembled in water/DMSO (75/25 vol/vol; 2 mg/mL) comprising amphiphilic diblock copolymers with a small amount of triazine-based guanine-cytosine (GCB) motifs incorporated in the hydrophobic block can undergo spontaneous rearrangement into new morphologies on mixing. For example, mixing spheres with vesicles resulted in spontaneous transformation into worms (nanofibers), and this transformation was accelerated at elevated temperature. The hydrogen bonding motif features three complementary hydrogen bonding sites on either side of the nucleobase unit, thereby having a Janus character. Amphiphilic diblock copolymers comprising dimethyl acrylamide (hydrophilic segment) and n-butyl acrylate (hydrophobic segment) were synthesized by reversible addition-fragmentation chain transfer (RAFT) polymerization with a variable content of acrylate monomer functionalized with the Boc-protected form of the GCB motif as part of the hydrophobic segment. The present work represents a completely new approach for controlling self-assembly processes, paving the way for the design of functional nanoparticles for a range of applications.